THE FEATURES OF THE INVESTIGATION OF THE TEXT: OFFICIAL STYLE - Karapetyan, Mariam (Foreign Languages for Special Purposes, 2024)
The present article is devoted to the investigation of the text belonging to the official style of the language which sets up a goal of exploring the main characteristics of the formal writing. The analysis involves the study of the special vocabulary and syntax which distinguishes the official from other types of writing. Formal, impersonal tone, precise terminology, specific syntax, accuracy, reliability-these are the key features of the official style of writing.